Legal Formulation for Forced Marriage Prevention through the Decision of Wali Mujbir in Religious Courts and its Relevance with Maqȧṣid Syari‘ah and Human Rights - Halim, Ahmad Rasyidi; Al Amruzi, M. Fahmi; Jalaluddin, Jalaluddin (Fakultas Syariah UINSI Samarinda, 2024)
Based on the Annual Report of the Indonesian Religious Court and Religious Court Decisions throughout Indonesia year 2020-2021, there were 5,080 divorces caused by forced marriages and 3446 divorces caused by arranged marriages without the basis of love. The number of cases shows that the practice of forced marriages and arranged marriages without love is still rife, which is the cause of divorce in society. Based on this background, this research probes efforts to prevent forced marriages through religious courts by proposing the wali mujbir prevention norm in the marriage law. Through this norm, children or parties under guardianship can file a case to the Religious Court to prevent forced marriages they are experiencing. This study shows that creating the wali mujbir prevention norm in the marriage law aims to accommodate the role of children actively, directly, and independently to prevent forced marriages against themselves by marriage guardians. If the marriage guardian is proven to have taken forced actions to marry off a child or person under his guardianship, then the marriage guardian is declared a wali mujbir, as stated in the ruling of the religious court. This proposal is one of the efforts to reduce the high number of divorces in society.